2012
DOI: 10.1136/bmj.e2124
|View full text |Cite
|
Sign up to set email alerts
|

Lung protective mechanical ventilation and two year survival in patients with acute lung injury: prospective cohort study

Abstract: Objective To evaluate the association of volume limited and pressure limited (lung protective) mechanical ventilation with two year survival in patients with acute lung injury.Design Prospective cohort study.Setting 13 intensive care units at four hospitals in Baltimore, Maryland, USA.Participants 485 consecutive mechanically ventilated patients with acute lung injury.Main outcome measure Two year survival after onset of acute lung injury.Results 485 patients contributed data for 6240 eligible ventilator setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
240
0
11

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 301 publications
(265 citation statements)
references
References 39 publications
(48 reference statements)
10
240
0
11
Order By: Relevance
“…In subjects with mild ARDS, the mortality was 27.2% in the higher-PEEP group and 19.4% in the lower-PEEP group (adjusted relative risk 1.37, 95% CI 0.98 -1.92). This analysis suggests that treatment with lower PEEP should be used with mild ARDS, and higher PEEP should be used with moderate and severe ARDS (P aO 2 5. Evidence is not currently available to suggest that one approach to setting PEEP leads to better outcomes than other approaches.…”
Section: Higher Versus Lower Peep: the Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In subjects with mild ARDS, the mortality was 27.2% in the higher-PEEP group and 19.4% in the lower-PEEP group (adjusted relative risk 1.37, 95% CI 0.98 -1.92). This analysis suggests that treatment with lower PEEP should be used with mild ARDS, and higher PEEP should be used with moderate and severe ARDS (P aO 2 5. Evidence is not currently available to suggest that one approach to setting PEEP leads to better outcomes than other approaches.…”
Section: Higher Versus Lower Peep: the Evidencementioning
confidence: 99%
“…Subsequent studies have confirmed a survival benefit for low V T ventilation. 5,6 Some studies have reported regional overdistention even with P plat Ͻ30 cm H 2 O, suggesting that there might not be a safe P plat . 7,8 Thus, the lungs should be ventilated with P plat as low as possible.…”
Section: Introductionmentioning
confidence: 99%
“…DOI: 10.4187/respcare.04644 Studies investigating the long-term outcomes within 1 y after ARDS Weinert (1997) 14 HRQOL: SF-36 6-41 mo (median 15 mo) after diagnosis HRQOL: all domains were below those of general population with similar physical difficulties to out-patients with chronic medical condition, but more deficits in social and mental domains Desai (1999) 19 Radiological findings 110-267 d (mean 196.2 d) CT scan: reticular pattern with anterior distribution was the most frequent abnormality (85% of subjects), related to duration of ventilation Angus (2001) 16 Survival 6-12 mo 55.7 Ϯ 3.7% at 6 with no change at 12 mo Neuropsychological disability Depression, anxiety, or insomnia in 46% of subjects; cognitive impairment in 21% Nöbauer-Huhmann (2001) 20 Pulmonary function 6-10 mo PFT: mild restrictive pattern (33% of subjects), mild obstructive pattern (33% of subjects) Radiological findings CT scan: lung fibrosis in 87% of subjects; lesions were more represented in nondependent lung regions Herridge (2003) 21 Survival 3, 6, and 12 mo after ICU discharge 26 Pulmonary function 6 mo PFT: abnormality in 67% of subjects, restrictive pattern in 58% of subjects; D LCO mild-moderate impairment; 6MWT; 60-65% of predicted distance Radiological findings CT scan: the extent of lung lesion was Ͻ25% of total lung volume in non-dependent regions (continued) and long-term follow-up characterized by a high mortality rate. 18 To quantify this survival gap, Wang et al 28 compared short-and long-term mortality in subjects with ARDS. Hospital mortality was significantly lower (24%) than 1-y mortality after hospital discharge (41%) regardless of the etiology of ARDS.…”
Section: Long-term Mortalitymentioning
confidence: 99%
“…[10][11][12] However, patients who survive ARDS remain at risk for mortality and may have persistent morbidity. [13][14][15][16][17][18] This article will review the long-term outcomes after ARDS, focusing on mortality, health-related quality of life (HRQOL), neuropsychological disability, radiological findings, and pulmonary dysfunction (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Poor compliance with ventilation strategy guidelines/expert opinions can be seen throughout the literature. 9,10 Because the time to irreversible injury is short, prompt recognition of abnormal V T is imperative. 3 Minimizing ventilator-induced lung injury is an integral part of patient care in the modern ICU.…”
Section: Introductionmentioning
confidence: 99%